2021
DOI: 10.1371/journal.pone.0249464
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of bubonic plague in Pernambuco, northeast of Brazil: Case study in the municipality of Exu

Abstract: Along with other countries in America, plague reached Brazil through the sea routes during the third pandemic. A brief ports phase was followed by an urban phase that took place in smaller inland cities and finally, it attained the rural area and established several foci where the ecological conditions were suitable for its continued existence. However, the geographic dispersion of plague in Brazil is still poorly studied. To better understand the disease dynamics, we accessed satellite-based data to trace the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The plague reappeared in rural areas after a six-year inter-epizootic period and disseminated among the wild fauna practically throughout the municipality territory. According to Figure 3A-F, the dispersal area of the rodents in the present study overlapped with the sites of the distribution of the human cases shown by Fernandes et al [11].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The plague reappeared in rural areas after a six-year inter-epizootic period and disseminated among the wild fauna practically throughout the municipality territory. According to Figure 3A-F, the dispersal area of the rodents in the present study overlapped with the sites of the distribution of the human cases shown by Fernandes et al [11].…”
Section: Discussionsupporting
confidence: 80%
“…In a previous study in this same plague area, the transition of the infection from urban to rural areas was observed [ 11 ]. The plague reappeared in rural areas after a six-year inter-epizootic period and disseminated among the wild fauna practically throughout the municipality territory.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations